Does Internet Usage Frequency Give Impact to Student’s Academic Performance? - Al Fariz, Arif Budiman; Lestari, Citra Ayu; Cahyo, Septian Dwi (Pusat Asesmen dan Pembelajaran, 2020)
In the last decade, the development of technology has been growing rapidly. Internet—as a part of technology—became one of the very important things for many people. The usage of internet had been increasing in the last few years. It happened to people with various backgrounds and ages around the world. There is an interesting phenomenon that nowadays internet usage behavior is not only happened to adult but also happened to student at school. Some studies have found that internet usage had negative effect on student’s academic performance. But another study emphasized that positive internet usage behavior gave significant effect on academic outcome. In this study, we distinguish internet usage behavior into two categories, viz. general internet user and professional internet user. General internet user refers to internet usage behavior that focus on communication and entertaining purposes. Otherwise, professional internet user refers to productive activities in using internet like searching for information and doing some works that are relevant to assist finishing academic’s tasks. This study aims to find the influence of internet usage—general and professional—on student’s academic performance in Indonesia. Internet usage behavior measured by 2019 Student’s National Examination Survey from Center for Educational Assessment Indonesia. While, student’s academic performance represented by 2019 Indonesian National Examination Score. In addition, studies found that student’s socio-economic status (SES) had influence on their pattern of internet use. Then, this study determined SES as control variable in order to find comprehensive explanation about impact of internet usage on student’s academic outcome.